Studies on TERRA : telomeric repeat containing RNA - Reelina Basu (2015)
In this study, we first developed a robust RNA-DNA FISH method for direct observations on the co-localization pattern of Terra and telomeric DNA in the nuclear context To understand the role of Terra in vivo, we monitored X chromosome telomere length change over a long-term cell culture of mouse ES cells and directly compared the length of Terra associated and non-associated telomeric ends. We observed an absence of telomere shortening upon Terra association with telomeric ends in vivo. Next, we attempted to identify transcriptional regulators of Terra. By using shRNA knockdown, we detected a role of CTCF and Rad21 in regulating Terra expression in cells. We also detected the presence of Terra in malaria parasite by Northern blot, RNA FISH and RNase protection assay.